Safe inter‐hospital ground transfer in the prone position of a critically ill patient with acute respiratory distress syndrome. Issue 1 (20th April 2017) - Honan, David Michael; Mohammed, Amr
Summary: Prone positioning to optimise ventilation in a patient with acute respiratory distress syndrome (ARDS) is not a contraindication to inter‐hospital transfer, and may be life‐saving. Basic safety precautions must be maintained throughout the transfer. Based on a successful case of prone transfer, we would advocate that transport teams consider training specifically for this scenario.